Effect of Dry Heat Puffing on Nutritional Composition, Fatty Acid, Amino Acid and Phenolic Profiles of Pseudocereals Grains - Paucar-Menacho Luz María; Dueñas Montserrat; Peñas Elena; Frias Juana; Martínez-Villaluenga Cristina (Polish Journal of Food and Nutrition Sciences)
The impact of puffing on nutritional composition and phenolic profiles of kiwicha (Amaranthus caudatus L.) and quinoa (Chenopodium quinoa Willd.) was investigated. Popped kiwicha showed increased protein and lipid contents and lower contents of carbohydrates compared to the untreated grains. Higher lipid, ash and carbohydrates contents and a decreased protein content were observed after puffing of quinoa. Fatty acid profile and ω-6/ω-3 ratio was not affected by puffing, although it was observed a healthier ratio in quinoa (7:1) compared to kiwicha (65:1). Thermal treatment reduced essential amino acid contents and protein quality of both grains, although amino acids content remained adequate according to FAO/WHO requirements for adults. Puffing decreased hydroxybenzoic and hydroxycinnamic acids content of both pseudocereals. Flavonoid levels were negatively affected by puffing in kiwicha while a noticeable increase was observed in popped quinoa. In summary, puffing of kiwicha and quinoa grains is an alternative processing method to obtain expanded products or precooked flours of adequate nutritional value.